19.8k views
5 votes
If f(n) = 2n + 1 and g(n) = 3n, find f(n) + g(n).

1 Answer

5 votes

Final answer:

To find f(n) + g(n), substitute the given expressions for f(n) and g(n) into the expression and simplify by combining like terms. The resulting expression is 5n + 1.

Step-by-step explanation:

To find f(n) + g(n), we need to substitute the given expressions for f(n) and g(n) into the expression.

f(n) + g(n) = (2n + 1) + (3n)

Simplify by combining like terms:

f(n) + g(n) = 2n + 1 + 3n = 5n + 1

Therefore, f(n) + g(n) = 5n + 1.

User Artych
by
5.4k points